Phytoremediation Potential of Azolla microphylla and Salvinia molesta for Copper (Cu) Removal: Effects on Biomass, Antioxidant Activity, and DNA Integrity - Sutan Nur Chamida Tri Astuti; Andhika Puspito Nugroho (Journal of Biotechnology and Natural Science, 2026)
Industrial wastewater represents a major source of environmental pollution, primarily due to the presence of heavy metals that pose significant risks to human health. Copper (Cu) is an essential trace element; however, its occurrence at elevated concentrations in aquatic environments can exert toxic effects. The aquatic plants Azolla microphylla and Salvinia molesta are known to possess potential as phytoremediation agents for heavy metal contamination. This study aimed to evaluate the effectiveness of these plants in reducing Cu concentrations, to quantify biomass production, to analyze the activity of the enzyme superoxide dismutase (SOD), to detect DNA damage using the comet assay, and to assess changes in water quality following treatment. Phytoremediation was conducted using a static system at Cu concentrations of 0, 10, 25, 50, 75, and 100 ppm. Data were analyzed using one-way ANOVA at a 95% confidence level. The results demonstrated that Azolla microphylla reduced Cu concentrations by up to 95.32%, whereas Salvinia molesta achieved a reduction of 72.42%. Plant dry biomass tended to decrease with increasing Cu concentrations, while metal accumulation within plant tissues increased. SOD enzyme activity did not show a significant increase, and no DNA damage was detected in leaf tissues, indicating the absence of severe oxidative stress. Furthermore, dissolved oxygen (DO) levels increased after 14 days of treatment. In conclusion, Azolla microphylla and Salvinia molesta exhibit strong potential as effective phytoremediators for Cu heavy metal contamination in aquatic environments.